The effectiveness of the use of Energia-M growth regulator in the protection system of winter wheat - Artemieva, E. A.; Zakharova, M. N.; Rozhkova, L. V. (Agrarnai͡a︡ nauka Evro-Severo-Vostoka, 2021)
In the formation of the winter wheat yield, the protection of the crop from pests, stress, pesticides and adverse abiotic factors is one of the important elements of the technology. To increase yield and reduce the impact of adverse factors in winter wheat protection systems, plant growth regulators are used. In the conditions of the Ryazan region in 2019-2020, the effectiveness of the use of tank mixtures of pesticides with the growth regulator Energia-M (0.01 kg/ha) in the protection systems of winter wheat of the Danaya variety was studied. In the variant with the use of a tank mixture of pesticides with a growth regulator, a statistically significant excess of yield was noted in comparison with the control (without treatment) by 1.4 t/ha (31 %) and with the variant with treatment using a tank mixture without the use of a growth regulator - by 0.9 t/ha (18 %). Under the influence of the plant growth regulator, a decrease in the negative impact of pesticides on growth processes, an increase in crop yield by 18 % due to the formation of an additional number of productive stems (80 pcs / m2 ) were noted and a higher net operating profit was obtained compared to the protection system without a plant growth regulator.